AC093797.1 as a Potential Biomarker to Indicate the Prognosis of Hepatocellular Carcinoma and Inhibits Cell Proliferation, Invasion, and Migration by Reprogramming Cell Metabolism and Extracellular Matrix Dynamics - Liu, Xiaoling; Wang, Chenyu; Yang, Qing; Yuan, Yue; Sheng, Yunjian; Li, Decheng; Ojha, Suvash Chandra; Sun, Changfeng; Deng, Cunliang (Frontiers in Genetics, 2021)
Abstract: Purpose: The risk signature composed of 4 lncRNA (AC093797.1, POLR2J4, AL121748.1, and AL162231.4.) can be used to predict the overall survival (OS) of patients with hepatocellular carcinoma (HCC). However, the clinical significance, biological function of AC093797.1 are still unexplored in HCC or any other malignant tumor. In this study, we aimed to investigate the biological function of AC093797.1 in HCC and screen the candidate hub genes and pathways related to hepatocarcinogenesis. Methods: RT-qPCR was employed to detect AC093797.1 in HCC tissues and cell lines. The role of AC093797.1 in HCC evaluated via the Cell-counting Kit-8, Transwell and wound healing assays. The effects of AC093797.1 on tumor growth in vivo was clarified by nude mice tumor formation experiments. Then, RNA-sequencing and bioinformatics analysis based on subcutaneous tumor tissue were performed to identify the hub genes and pathways associated with HCC. Results: The expression of AC093797.1 decreased in HCC tissues and cell lines, and patients with low-expression AC093797.1 had poor OS. AC093797.1 overexpression impeded HCC cell proliferation, invasion, and migration in vitro, and suppressed tumor growth in vivo. By RNA-sequencing, 710 differentially expressed genes (243 up-regulated genes and 467 down-regulated genes) were filtered between groups, which mainly enriched in amino acid metabolism，extracellular matrix structure constituent, cell adhesion molecules cams，signaling to Ras, and signaling to ERKs, etc. Conclusion: AC093797.1 can inhibits cell proliferation, invasion, and migration via reprogram cell metabolism or regulating several pathways in HCC, suggesting AC093797.1 might be a potential therapeutic and prognostic marker for HCC patients.